Construction of The Social Reality of Idealism Digital Era Journalists in Banten - Sjuchro, Dian Wardiana; Yusanto, Yoki; Amdan, Nana Sutisna; Muhaemin, Muhaemin; Ramadhan, Aditya (Jogjakarta Communication Conference (JCC), 2023)
In Banten Province, news portals or online media are growing rapidly. There are hundreds of active online media, including; Mainstream media such as the Jawa Pos Group, Radar Banten, Banten Raya Pos, and Kompas, namely the Tribune Network. The research approach was carried out qualitatively, with descriptive analysis techniques. The data was obtained from in-depth interviews with informants who are online journalism practitioners in Pandeglang Regency, Lebak Regency, Serang City and Tangerang City, Banten Province. To convince the fact from the interview, the researcher conducted a literature study related to the locus of problems in this study. In addition, this study applied the elaboration of theory from Peter Berger and Thomas Luckmann through their book entitled The Social Construction of Reality: A Treatise in The Sociology of Knowledge (1996). The results of this study highlighted the condition of mass media companies which must be able to adapt to developing technology, including the working pattern of journalists. Online journalism demands Human Resources (HR) that are in accordance with the internet operating system because apart from journalism-based online media there is also social media whose operating system grafts onto conventional journalism. Journalists in Banten Province still adhere to the Basic Press Law Number 40 of 1999 and cyber media guidelines in their work. In addition, journalists in Banten still uphold professionalism by prioritizing ideaslime based on Akhlakul Karimah (good behaviour) when working.